GOAL-SETTING AND FREEDOM AS CHATACTERISTICS OF HUMAN ACTIVITY - DEMIRTSHYAN, MOVSES (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The article states that processes at different levels of the organization of life – non-organic, organic and social, are influenced by different laws. Inorganic life proceeds according to the law of necessity, organic life – by the law of expediency, and social – by goal-setting. However, goal-setting as a conscious activity is inherent only to an individual, which means, that social institutions and various spheres of social life continue to “live” according to the law of expediency. This partly explains the wellknown conservatism of such spheres of social life as economics, politics, education, etc. Goal-setting, as the most characteristic feature of an individual’s activity, is closely related to such phenomena as freedom and responsibility. It is substantiated that in goalsetting, as in the conscious activity of an individual, the metaphysical content of freedom and responsibility is concretized and finds its “visible” expression.